Union of South Africa Debates of the House of Assembly Second Session, Fifth Parliament 1925 - South Africa Parliament (Cape Town Government Printer, 1925)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times.
Debates of the House of Assembly Union of South Africa. Fourth Session, 4th Parliament, vol. 1 (25 Jan.-10 Apr. 1924)-4th Session, 12th Parliament, v. 108 (1 May-26 May 1961).
Keywords: Second Session - Fifth Parliament; 1925; JC044665; 16 April; 11 June; Index to Subject; House of Assembly; Union of South Africa; Debates; Hansard